Psychological Empowerment Of Agent Of Change: Case Study In Public Sector Organization - Oktaviani, Mimy; Dahesihsari, Rayini (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
Many studies show that the process of change does not always have the expected impact if not managed thoughtfully. One of the key actors in managing the change process is an agent of change. Studies on organizational change generally focus on the organization and readiness of the people to change. There is not much attention is given to studying the agent of change. Even though they are important actors responsible for initiating, facilitating, and evaluating means of adjustment (Smither et al. (2016)).This study focuses on the psychological empowerment of change agents, which are required in the role to overcome various obstacles and constraints in initiating and implementing change (Bowen and Lawler (1992), The study was conducted in the public sector in Jakarta using a qualitative approach. Depth interviews were conducted among three employees of an organization designated as a member of the team changes, to explore their thoughts, appreciation, and sense of competence that they have to implement the changes and overcome the challenges and obstacles. The results showed that participants appreciate their role as agents of change because of the removal of their boss, feel the task is part of them, and see the positive impact of their role in bringing a positive difference to the organization. They generally feel quite able to perform their purpose well enough, though still in need of capacity building continuously throughout the process of change. However, Others experience a significant task in the role of agents of change, and participants generally feel that they can not perform their function optimally because of the limitations of their authority. Excellent coordination skills required for this condition so that each unit can be encouraged to get a more integrative perspective on organizational change.